PERLINDUNGAN HUKUM ATAS HAK UPAH PEKERJA PADA HOME INDUSTRI - Sefryndo Krisna E.H (Gapenas Publisher, 2022)
Home industry or what is commonly called a home industry, which carries out production activities at home on a not large scale, such as an industry in a factory. The existence of a home industry itself makes it easier for people to find work in order to get wages for the necessities of life. As workers sometimes ordinary people do not know their rights as workers that must be fulfilled. For example, the fulfillment of wage rights for workers sometimes has problems that make workers suffer losses, where what happens is that the wages given do not match what the workers do. So that workers need to protect their rights so that there is no discrimination by business actors. Therefore, the author wants to solve a problem that often occurs, the formulation of the problem proposed is as follows: 1. How is the legal protection for unfulfilled wage rights? 2. What are the legal consequences for business actors who do not fulfill their rights to workers' wages? The research method used is normative by using a statutory approach with a conceptual approach method. The results of this study prioritize knowing the rights of workers that must be fulfilled by business actors, with this so that workers will understand their rights that must be fulfilled. Therefore, home industry workers are vulnerable to discrimination, so their rights need to be protected